Corporate governance in Colombian universities - Florez-Parra, Jesus Mauricio; Lopez-Perez, Maria Victoria; Lopez-Hernandez, Antonio Manuel (International Review of Administrative Sciences)
In a context of greater demands in terms of accountability and transparency in management, we analyse the extent to which Corporate Governance (CG) mechanisms have been adopted and we define the model of governance in universities in Colombia. In the field of higher education, there are usually no compulsory requirements related to CG. Nevertheless, governance mechanisms are nowadays crucial in determining the objectives, strategies and direction of universities. Based on a survey of 81 rectors of higher education institutions in Colombia, we analyse the models of CG adopted (managerial and stakeholder models). The results contribute to a better understanding of key CG concepts at universities. - Reproduced.